Switchable asymmetric bio-epoxidation of α, β-unsaturated ketones. Issue 6 (24th November 2015) - Liu, Yu-Chang; Wu, Zhong-Liu
Abstract : Efficient asymmetric bio-epoxidation of electron-deficient α, β-unsaturated ketones was realized via a tandem reduction-epoxidation-dehydrogenation cascade in a switchable manner. Abstract : Efficient asymmetric bio-epoxidation of electron-deficient α, β-unsaturated ketones was realized via a tandem reduction-epoxidation-dehydrogenation cascade, which proceeds in a switchable manner to afford either chiral epoxy ketones or allylic epoxy alcohols with up to >99% yield and >99%ee.